The Impact of Ethics Education on Teachers' Professional Development and Its Influence on Decision Making, Classroom Practices, and Teacher-Student Relationships - Nasir, Nasir; Awaluddin, Awaluddin; Ashar, Ashar (Educia Journal, 2024)
This study explores the role of ethics education in the professional development of teachers, focusing on how it influences their teaching practices, decision-making, and professional behavior. Using a qualitative research design, data were collected through semi-structured interviews, focus group discussions (FGDs), and document analysis involving 15 teachers from diverse educational backgrounds in Makassar City, Indonesia. The findings reveal that ethics education significantly enhances teachers’ ability to navigate ethical dilemmas in the classroom, fosters positive teacher-student relationships, and promotes collaboration among colleagues. Teachers reported that ethics training equipped them with the tools to handle challenges such as fairness in student discipline, respect for cultural diversity, and digital privacy concerns. However, the study also identified gaps in the consistency and continuity of ethics education programs, with many teachers emphasizing the need for ongoing training and peer support. The study contributes to the literature by addressing the gap in understanding how ethics education is applied in real-world teaching contexts and its long-term impact on teachers’ professional development. It highlights the importance of integrating ethics education into continuous professional development programs, ensuring that teachers are equipped to handle evolving challenges in education. This research provides valuable insights for educators, policymakers, and institutions seeking to improve ethical standards and support teacher growth.